Implementing Evidence-Based Occupational Therapy for Multiple Sclerosis Rehabilitation: Exploring Knowledge on Barriers, Facilitators and Strategies - De Coninck, Leen; Boers, Ashley; O’Meara, Ciara; E Bekkering, Geertruida; Koen, Marja; Freeman, Jennifer; M Hynes, Sinead; CJM Eijssen, Isaline; Sayfullaeva, Jessica; Kos, Daphne (Journal of Implementation science, 2026)
Background A persistent gap remains between evidence-based health care and its application in routine practice. This challenge is particularly prominent in allied health professions like occupational therapy (OT), where interventions are complex, individualized and centred on patients' daily functioning. Objective To identify barriers, facilitators, and implementation strategies for integrating evidence-based OT interventions in multiple sclerosis (MS) rehabilitation. Methods A mapping review was conducted using searches in five databases. Eligible studies included adults with MS, examined OT interventions, and reported on factors influencing implementation. Data were extracted and categorized using Grol’s framework for barriers/facilitators and Mazza’s taxonomy for implementation strategies. Results Fifteen studies met inclusion criteria. Barriers and facilitators were identified at multiple levels of Grol’s framework: 1-Innovation-level: accessibility, feasibility, and perceived attractiveness supported implementation, particularly when interventions incorporated holistic approaches, gamification, or printed manuals. 2-Professional-level: therapists’ competencies and alignment between interventions and patients’ priorities. 3-Patient-related: facilitators included motivation, readiness to change, and peer support, whereas fatigue, pain, and cognitive challenges served as barriers. 4-Social and organizational: effective teamwork, resource availability, and flexible scheduling facilitated successful adoption. 5-Economic or political: no studies. Implementation strategies focused on using manuals, patient empowerment, gamification, and organizational supports. No financial or structural policy-level strategies were identified. Conclusion Successful implementation of evidence-based OT for MS requires multifaceted, context-sensitive strategies addressing innovation, professional, patient, and organizational determinants. Practical approaches enhance uptake, while substantial gaps persist at economic and policy levels. Strengthening these areas may improve longterm integration and sustainability of evidence-based OT in MS rehabilitation.
Keywords: Implementation; barriers and facilitators; evidence-based practice; knowledge translation; multiple sclerosis; occupational therapy